Methodology of collecting membrane samples of pericardium from rats. Anatomical and topographical features of rat pericardium - Verba , E.I.; Kushch , O.G. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. While the anatomy of all mammalian species is generally similar, there are significant differences that have not been sufficiently explored. During embryogenesis, two cavities, thoracic and peritoneal, are formed from the primary celom. The mediastinum is primarily formed within the thoracic cavity, and only then does organogenesis occur. It makes the structure of pericardium similar to the primary celom. Despite advancements in the study of human pericardium anatomy, pericardium of laboratory animals have not received adequate attention. This fact motivated further research of rat pericardium. Objective. The objective of this study is to refine the methodology of collecting membrane sampless of rat pericardium for subsequent histological studies. Develope an algorithm and provide a detailed description of the procedure. Additionally, it aims to identify and study the anatomical and topographical characteristics of rat pericardium. Methods. This research was conducted on 5 sexually mature male laboratory rats from the vivarium of the Biology Department at Zaporizhzhia National University. An improved methodology of collecting membrane samples is described in the form of an algorithm, allowing to take an exactly isolation membrane of pericardium for research, rather than studying it as part of a complex of organs. Results. The research revealed anatomical, topographical, and morphological features of rat pericardium, including their topographical location within the mediastinum, absence of adhesions to other pleural organs, and the presence of a single sterno-pericardial ligament. Conclusions. The obtained research data can significantly impact the course of experimental scientific studies related to the heart. Therefore, it should be considered in developing scientific experimental models with laboratory animals.